Electrically Tunable Gap Surface Plasmon-based Metasurface for Visible Light. Issue 1 (December 2017) - Guo, Jingjing; Tu, Yan; Yang, Lanlan; Zhang, Ruiwen; Wang, Lili; Wang, Baoping
Abstract In this paper, an electrically tunable metasuface is designed for visible regime. The device mainly consists of a V-shaped metallic metasurface, an ITO film,  an electro-optic (EO) dielectric and a metal layer fabricated on a silica substrate. A continuous electrical modulation of resonant wavelength has been theoretically demonstrated in the visible range from 555 nm to 640 nm by changing the voltage applied on the EO dielectric from −20 V to 20 V. During the modulation, the steering angle also changes with the selective color. The peak cross-polarized reflectivity is higher than 48% and the bandwidth is narrower than 60 nm. The resonant wavelength shift can be explained by that the refractive index variation of the EO material induces resonance condition changes of the gap surface plasmon (GSP). The results provide a novel design solution for active plasmonic devices, especially for dynamic metadevices.